Computing antimicrobial use/antimicrobial resistance ratios: A novel way to assess inpatient antimicrobial utilization using current National Healthcare Safety Network metrics. Issue 5 (18th October 2022) - Santos, Carlos A. Q.; Martinez, Ashley I.; Won, Sarah Y.; Varughese, Christy A.; Tseng, Marion; Zhang, Huiyuan; Trick, William E.
ABSTRACT: Background: Current methods for benchmarking inpatient antimicrobial use (AU) could benefit from combining AU with antimicrobial resistance (AR) information to provide metrics benchmarked to microbiological data; this may yield more instructive and better risk‐adjusted measurements than AU and AR in isolation. Methods: In this retrospective single‐center study, we computed facility‐wide AU/AR ratios from 2019 to 2020 for specific antimicrobial agents and corresponding AR events, and compared median monthly AU/AR ratios between March 2019 through December 2019 (pre‐COVID period) and March 2020 through December 2020 (COVID period). Aggregate AU was expressed as a ratio to aggregate AR events for antimicrobials that typically have activity against the AR organism and are frequently used to treat the AR organism in clinical practice. We also computed AU/AR ratios in our surgical intensive care unit in the pre‐COVID period. Results: High‐median facility‐wide monthly AU/AR ratios were observed for intravenous vancomycin/methicillin‐resistant Staphylococcus aureus, with 130.0 in the pre‐COVID period and 121.3 in the COVID period ( p =.520). Decreases in facility‐wide median monthly AU/AR ratios were observed between periods for meropenem/ESBL Enterobacterales (20.9 vs. 7.9, p < .001), linezolid/vancomycin‐resistant Enterococcus (48.5 vs. 15.8, p =.004), and daptomycin/vancomycin‐resistant Enterococcus (32.2 vs. 4.8, p = .002). Increases in facility‐wide median monthly AU/AR ratios were observed between periods for ceftazidime‐avibactam/carbapenem‐resistant Enterobacterales (0.0 vs. 3.2, p = .020) and ceftazidime‐avibactam/multidrug‐resistant Pseudomonas aeruginosa (0.0 vs. 4.0, p = .017). The AU/AR ratio for intravenous vancomycin/methicillin‐resistant S. aureus in the surgical intensive care unit was 191.5 in the pre‐COVID period. Conclusions: AU/AR ratios may be used to supplement current AU and AR metrics. Future directions should include the development of more AU metrics benchmarked to microbiological information. AU metrics more specific to transplant infectious diseases should be developed.